Implementation of Magic Box Media for Early Childhood Symbolic Thinking - Dewi Saputri, Indri; Purnama, Sigit (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
The importance of early childhood education cannot be separated from its role in forming the basis for the development of various aspects of a child's life. At this stage, children begin to get to know the world around them, develop social interaction skills, and build the cognitive foundations they will use in the future. The ability to think symbolically is the basis for children to understand and process more complex information in the future. Through this ability, children begin to develop the ability to imagine, solve problems and think abstractly. The research used is qualitative descriptive research. The research location is TK Aisyiyah 02 Tambakromo. The number of subjects in this study was 23 people. The data in this research was collected through several techniques, namely observation, interviews and documentation. The data obtained in this research was collected and analyzed using thematic analysis techniques with data analysis steps including Data Reduction, Data Presentation, and Drawing Conclusions. The results obtained are that the use of learning media is very necessary in helping early childhood understanding. Based on the data obtained, the implementation of magic box media can improve students' symbolic abilities as evidenced by the fact that all students are in the criteria of developing according to expectations (BSH) and developing very well (BSB).